Implementing Reverse Logistics Optimization in Hazardous Waste Frameworks: Bridging Practice and Strategy - Li, Huilin; Yang, Jiaqi; Zhang, Wei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Cruise construction entails a protracted logistical cycle, intricate processes, and a vast assortment and quantity of raw materials and intermediate products. Inevitably, reverse materials are generated. To mitigate the potential for stock occupation, production impact, and occupational safety risks stemming from reverse materials, a novel optimization model for reverse logistics networks is proposed, which integrates cost, efficiency and risk factors from a health, safety and environment (HSE) management perspective, adopts a fuzzy operating time window to reflect safety satisfaction, and proposes a three-phase Levy mutation-based Discrete Crow Search Algorithm (DCSA) to derive green, efficient and safe scheduling schemes. The model is able to optimize the allocation of transport vehicles, path planning and risk assessment to improve operational efficiency and safety. To enhance the realism of the model, this paper considers factors such as vehicle load, transport cost, loading time and risk weight, which ultimately achieves better transport efficiency and safety. As well as comparing it with a cost-only scenario, the results show that although cost-oriented scenarios may provide economic benefits in the short term, they tend to ignore the risks that may lead to long-term consequences. This underscores the importance of incorporating safety considerations into operational planning and validates the effectiveness of the model and methodology.